2012
DOI: 10.1155/2012/215876
|View full text |Cite
|
Sign up to set email alerts
|

Dioxaphosphorinane-Constrained Nucleic Acid Dinucleotides as Tools for Structural Tuning of Nucleic Acids

Abstract: We describe a rational approach devoted to modulate the sugar-phosphate backbone geometry of nucleic acids. Constraints were generated by connecting one oxygen of the phosphate group to a carbon of the sugar moiety. The so-called dioxaphosphorinane rings were introduced at key positions along the sugar-phosphate backbone allowing the control of the six-torsion angles α to ζ defining the polymer structure. The syntheses of all the members of the D-CNA family are described, and we emphasize the effect on seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 72 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…In silico -C2NA structure conformational study As previously observed with -CNAs, 9,12,14 among the four possible -C2NAs isomers, only two of them can have all the substituents of the phosphorinane ring in the orientation that favours their formation, stability and conformational interest: the upper nucleoside in the apical position, the exocyclic oxygen and the lower nucleoside in equatorial position. Moreover in line with the results obtained with their -CNA analogues, a simple molecular model examination indicated that this couple should mainly differ on the  torsional angle conformation.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In silico -C2NA structure conformational study As previously observed with -CNAs, 9,12,14 among the four possible -C2NAs isomers, only two of them can have all the substituents of the phosphorinane ring in the orientation that favours their formation, stability and conformational interest: the upper nucleoside in the apical position, the exocyclic oxygen and the lower nucleoside in equatorial position. Moreover in line with the results obtained with their -CNA analogues, a simple molecular model examination indicated that this couple should mainly differ on the  torsional angle conformation.…”
Section: Resultsmentioning
confidence: 80%
“…The first was directed towards the development of nucleotides in which the sugar/phosphate backbone geometry was constrained (Constrained Nucleic Acids: CNAs) in order to propose nucleotides analogues able to fit either with the B-DNA canonical structure or others non-helical relevant disparate secondary structures. 9 The second research axis was oriented towards the design of convertible nucleotides where an appended arm at the C5' position was bearing an orthogonally reactive function such as an alkyl halide or alkyne. 10 Here we present our effort to merge these two approaches in the development of a combination of the two properties into one family of dinucleotides: the Constrained and Convertible Nucleic Acid (C2NA).…”
Section: Introductionmentioning
confidence: 99%
“…Our seminal approach to D‐CNA synthesis was based on the steric and electronic control of an intramolecular cyclization involving displacement of a tosylate group through attack of a phosphate thio‐ or oxyanion linked to C‐4′‐ or C‐5′ . To install a sulfur or selenium atom onto a common phosphite intermediate for each D‐CNA, we chose to condense a thymidine phosphorodiamidite onto 4′‐ C ‐hydroxymethylthymidine 2 (for α,β,γ‐D‐CNA), and onto 5′‐ C ‐hydroxyethylthymidine 3 and 5 (for α,β‐D‐CNA) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…1). 4 Among the synthesized dioxaphosphorinane-constrained nucleic acid dinucleotides (D-CNAs), those featuring B-DNA canonical values for the torsional angles showed an improved duplex formation ability. 5 The behaviour of these constrained analogues was easy to understand in this study according to the preorganization concept, 8 and then could be selected as unnatural nucleoside analogs for antisense therapy.…”
Section: Introductionmentioning
confidence: 99%